What are essential elements of high-quality palliative care at home? An interview study among patients and relatives faced with advanced cancer - Oosterveld-Vlug, M. G. (BMC Palliat Care, 2019)
BACKGROUND: In the Netherlands, general practitioners (GPs) and community nurses play a central role in the palliative care for home-dwelling patients with advanced cancer and their relatives. To optimize the palliative care provision at home, it is important to have insight in the elements that patients and relatives consider essential for high-quality palliative care, and whether these essentials are present in the actual care they receive. METHODS: Qualitative semi-structured interviews were conducted with 13 patients with advanced cancer and 14 relatives. The participants discussed their experiences with the care and support they received from the GP and community nurses, and their views on met and unmet needs. Interview data were analysed according to the principles of thematic analysis. RESULTS: Patients as well as relatives considered it important that their GP and community nursing staff are medically proficient, available, person-focused and proactive. Also, proper information transfer between care professionals and clear procedures when asking for certain resources or services were considered essential for good palliative care at home. Most interviewees indicated that these essential elements were generally present in the care they received. However, the requirements of ‘proper information transfer between professionals’ and ‘clear and rapid procedures’ were mentioned as more difficult to meet in actual practice. Patients and relatives also emphasized that an alert and assertive attitude on their own part was vital in ensuring they received the care they need. They expressed worries about other people who are less vigilant regarding the care they receive, or who have no family to support them in this. CONCLUSIONS: Medical proficiency, availability, a focus on the person, proper information transfer between professionals, clear procedures and proactivity on the part of GPs and community nursing staff are considered essential for good palliative care at home. Improvements are particularly warranted with regard to collaboration and information transfer between professionals, and current bureaucratic procedures. It is important for care professionals to ensure that the identified essential elements for high-quality palliative care at home are met, particularly for patients and relatives who are not so alert and assertive.